Health Care Workers’ Knowledge, Attitude and Practice on COVID-19 in a Government Hospital, Biratnagar - Katuwal, Anjana; Bhandari, Menuka (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
World Health Organization declared COVID-19 as a global pandemic on 11th March 2020 due to rapid transmission and severity of illness of this fatal virus from the country of origin. This study was conducted to assess the health care workers’ knowledge, attitude and practice on COVID -19 in a government hospital at Biratnagar. A descriptive, cross-sectional research design was used. Census method was adopted for sampling, structured questionnaire was used to collect data among 115 healthcare workers over a period of two months. More than three fourth (78.3%) scored good knowledge, almost all possessed a positive attitude and more than half (62.6%) had good infection prevention practice on COVID-19. However, 52.2% reported that COVID-19 is contagious and only 13.9% identified as a zoonotic disease. Also, it revealed that only 35.7% practiced correct steps of donning PPE, only 27.8% reported proper sequence of doffing PPE and 40.0% followed standard duration for hand washing as per the WHO, CDC guideline. The study highlighted the gap in some specific aspects of knowledge and practice of the healthcare workers that need immediate concern. Adequate provision of periodically updated educational training programmes on COVID-19 and infection prevention practices focusing on PPE might help bridging the gap.